What Gets Measured Gets Managed : Assessing Public Financing for Improving Nutrition Outcomes and Human Capital in Bhutan - Ahmed, Shakil (World Bank, Washington, DC, 2019)
This study summarizes estimates and lessons learned from application of the scaling up nutrition (SUN) methodology to assess public financing for nutrition in Bhutan. Using Bhutan’s classification of nutrition interventions, per capita public financing for addressing malnutrition is estimated to be Nu 2,003 (approximately United States (U.S.) 29 dollars, 1 percent of gross domestic product (GDP), and 3 percent of total government expenditures), 30 percent of which was for nutrition-specific activities, and about one-third the level of public spending on health. The level of public spending for nutrition is similar in magnitude - and in the shares across nutrition-specific and nutrition-sensitive interventions - when compared with other developing countries; recent estimates from Asia indicated an average of 2 percent of aggregate government expenditures went toward addressing nutrition, with a 20 percent share for nutrition-specific interventions. Despite the level of spending increasing from Nu 1,744 in financial year (FY) 2013-14, there does not appear to be any increase in priority to nutrition over the course of the 11th five-year plan (FYP): increases in the levels of expenditure for nutrition have resulted from growth of the economy and not because of higher budget allocation to addressing nutrition. The largest nutrition-specific expenditures were those related to the national school feeding program and the largest nutrition-sensitive expenditures were those related to water, sanitation, and hygiene (WASH) programs. Notably, the financing locus for nutrition-related expenditures lies within the Ministry of Education (MoE) and the Ministry of Works and Human Settlement (MoWHS). Although Bhutan defines nutrition-specific and nutrition-sensitive interventions somewhat differently from how they are defined globally, the magnitude of resources allocated toward improving nutrition appears similar to those in other developing countries even when adjusted to enhance global comparability.